Integration of digital technologies to improve the efficiency of small and medium-sized agricultural enterprises - Zhanna Yermekova; Svetlana Romanenko; Gaukhar Zhanibekova; Bakytzhamal Aitzhanova; Nurlan Apakhayev (Наукові горизонти)
The purpose of the study was to assess the impact of the introduction of digital technologies on improving the efficiency of small and medium-sized agricultural enterprises in Kazakhstan. To achieve this goal, a set of methods was used, including statistical analysis, a comparative method, and content analysis of respondents' answers through questionnaires. The study results showed that the integration of digital solutions has significantly reduced management and production costs, reducing them by 12%. The introduction of digital technologies has helped to increase crop yields by 15% and improve the efficiency of agricultural production. In addition, digitalisation has reduced the time required to make managerial decisions by 20%, which has increased the efficiency of management processes. The use of ERP/CRM systems, agrotechnological platforms and business process automation positively correlated with increased profitability, with correlation coefficients of 0.45, 0.38 and 0.52, respectively, which is statistically significant (significance levels 0.01, 0.05, and 0.02). The ERP system (r = 0.62, p-value = 0.01) showed a particularly high correlation with energy efficiency, while automation (r = 0.55, p-value = 0.02) and agroanalysis (r = 0.47, p-value = 0.03) also made a significant contribution. Analysis of variance showed a statistically significant difference in profitability between enterprises that implement digital technologies (F-statistics 5.62, p-value 0.01) and those that do not use them (F-statistics 2.34, p-value 0.05). This confirmed the importance of digital transformation for improving business financial results. Thus, digital technologies significantly increase the efficiency and competitiveness of agricultural enterprises, which is confirmed by both quantitative and qualitative findings